PELATIHAN KETERAMPILAN MEMBUAT SLIDE PERSENTASI EFEKTIF DENGAN EFEK GRADASI PADA MAHASISWA FAKULTAS ILMU BUDAYA UNILAK - Loneli Costaner; Guntoro Guntoro; Lisnawita Lisnawita (Universitas Lancang Kuning, 2018)
Teaching and learning process is an integral in the achievement of human resources who have the skills in the field in accordance with the goals of a college. Students who undergo the study other than he get the knowledge in the field that he studied, will also be given the learning experience given the task by the lecturer supervisor of the course and then the results are feasible for the percentage of campus forums with tools and complete electronic media. Nowadays, the percentage becomes the obstacle by students to get the perfect score, because the percentage is related to the presentation slide which is interesting and easy to understand by the audience. The percentage slide also becomes an assessment at the moment of presentation in front of the class forum, the student is not yet understand how to make an interesting and effective presentation so that the idea is well conveyed. In addition, students also difficult to make a presentation with a combination of images and writing because it has not got the skills to design the slide so much the results of the presentation of what is with a fairly satisfactory percentage value. In today's digital age, it can be said that any profession of someone in the world of organization, both business world and academic world can not be separated from the necessity to do the exposure to explain the purpose of a problem or information. Ability to present good information with an attractive means is necessary to get the ideas and ideas to the person who received the information. Good presentation skills, interesting and informative is needed everyone so that ideas or ideas can be easily understood. One of the media presentations to make the ideas submitted so more informative and interesting is to use Ms. Power point.